Whys and Wherefores: The Aetiology of the Left Periphery (With Reference to Vietnamese) - Nigel Duffield (Languages)
This paper offers a detailed description of the left periphery of embedded clauses in Vietnamese. Five kinds of pre-subject constituent are considered in isolation, and in interaction with one another: subordinating conjunctions; embedded topics; fronted quantifier expressions; fronted adverbials, and the Vietnamese equivalent of English why (Italian perché). A systematic comparison is made with the functional sequence of Italian, proposed in the cartographic literature. Whilst largely consistent with the Italian pattern, our findings diverge in certain respects, especially in suggesting a modification of previous treatments of the *‘why-to’ constraint observed in English and a number of other varieties.